TEAM TEACHING MODELS AND PRIMARY SCHOOL PUPILS’ LEARNING OUTCOMES IN MATHEMATICS IN OYO, NIGERIA (2018)
Literature in mathematics education shows that the teaching methods being applied by many mathematics teachers are teacher-centered. Furthermore, the methods do not relate classroom activities to out of class real life experiences. Most often, low-achieving secondary school students (LASSS) do not gain from the method of instruction and consequently develop poor attitude towards mathematics, particularly in the area of Geometry. It is on the basis of this that the study examined the extent to which Out-of-Class-Activity (OCA) and Group Counselling Strategies (GCS) enhance learning outcomes in Geometry among LASSS in Ibadan, with students’ mathematics self-efficacy (MSE) and gender as moderator variables. A pretest, posttest control group experimental design with 3x2x2 factorial matrix was adopted for the study. Multistage random sampling technique was used to select 110 LASSS from six Junior Secondary Schools in three Local Government Areas in Ibadan. These students were distributed into three groups viz: Group I (OCA), Group II (GCS) and Group III (Control). Four validated instruments: Students’ Selection Test (r = 0.70); Achievement Test in Geometry (ATG) (r = 0.81); Mathematics Self-Efficacy Scale (r = 0.85); and Geometry Attitude Scale (GAS) (r = 0.73) were used to collect data. Seven hypotheses were tested at 0.05 level of significance. Data were analysed using Mean, Standard Deviation, and Analysis of Covariance. There was a significant main effect of treatment on achievement in Geometry (F (2, 97) = 35.77, p < 0.05) and attitude towards Geometry (F (2, 97) =108.21, p < 0.05). In ATG, OCA Group performed best ( = 19.10; SD =3.99) followed by GCS ( = 19.03; SD = 3.57), while Control Group performed worst ( = 12.58; SD = 3.75). In Geometry Attitude Scale, Out-of-Class-Activity group performed best ( =220.20; SD =28.58) followed by GCS ( =205.87; SD = 21.86), while Control Group performed worst ( = 157.92; SD = 27.40). Mathematics Self-Efficacy had statistically significant effect on achievement in Geometry (F (1, 97) = 4.07, p < 0.05), but no significant effect on attitude towards Geometry. Students who held strong beliefs in their abilities performed better ( = 17.27; SD = 5.13) than those who did not believe in their abilities ( = 16.05; SD = 4.58.). There was no significant difference between the male and female students in their achievement in and attitude towards Geometry. There were no significant 2 and 3-way interaction effects of treatment, gender and MSE on learning outcomes in Geometry. This implies that the effects of treatments on learning outcomes in Geometry can be generalised across male and female and students with low and high levels of mathematics self-efficacy. Both Out-of-Class-Activity and Group Counselling strategies were effective in enhancing learning outcomes in Geometry among low-achieving secondary students. Based on the efficacy of the interventions, mathematics teachers, counsellors and school administrators should employ these strategies in enhancing learning outcomes in Geometry among students.